Developing a Local Wisdom-Based Pop-Up Book to Enhance Elementary Students’ Critical Thinking Skills and Cultural Appreciation - Wahyu Tri Utami; Joko Sulianto; Joko Siswanto (STAI Hubbulwathan Duri, 2025)
Elementary Science and Social Studies (IPAS) instruction often lacks interactive and culturally relevant learning media, limiting students’ engagement and critical thinking. This study aims to develop a Pop-Up Book based on Rembang's local wisdom to enhance fourth-grade students’ critical thinking skills and cultural appreciation. The research employed a Research and Development (RD) approach using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Participants included two expert validators (material and media), two teachers, and 30 fourth-grade students from two public elementary schools in Rembang Regency. Data were collected through expert validation sheets, practicality questionnaires, classroom observations, and pretest–posttest assessments. Quantitative data were analyzed descriptively and using N-Gain scores, while qualitative data were examined thematically. The developed Pop-Up Book received a validity score of 95% from experts, indicating very high feasibility. Practicality ratings from teachers and students were 92.5% and 91.8%, respectively. The effectiveness test showed an increase in students’ critical thinking scores, with an average N-Gain of 0.67, categorized as moderate to high. Observational data also revealed increased student engagement, questioning, and cultural awareness during learning activities. The findings demonstrate that the Rembang local wisdom-based Pop-Up Book is valid, practical, and effective for IPAS learning. It provides contextual, engaging instruction that supports critical thinking development while fostering cultural identity in alignment with Indonesia’s Merdeka Curriculum.